(untitled) (Global Journal of Management and Business Research, 2014)
Ethical business attempts to establish justice to all of its stakeholders by satisfying their ethical desires. But lack of ethical desires of the stakeholders is a major hindrance to developing an ethical business. In a larger-scale-enterprise, owner, management, and accountant play vital role in initiating, establishing, and ensuring ethical guidelines for all of its stakeholders. In the way to ethical business development, one or two of these three parties are not able to ensure justice independently rather needs a mutual cooperation